A habitação de interesse social e o direito à cidade: entre os distritos de Cidade Tiradentes e Grajaú - Baltazar, Cristina Gomes (2021)
This thesis has as its goal to comprehend to what extent public housing initiatives guarantee the right to the city. To this end, it resorts to Henri Lefebvre's conception about the right to the city and to the public housing interpretation in the light of Buonfiglio’s thought as a need, demand, commodity, deficit, right and public policy. The studied time frames are delimited by the two main agents and/or public housing programs, the National Housing Bank of Brazil (BNH) and the My House, My Life program (PMCMV). The districts of "Cidade Tiradentes" and "Grajaú" were selected as the research field for being regions with high public housing concentration from both programs. The study portraits the relationship between public housing and the right to the city, guided by five analytical axes: urban infrastructure, residential comfort, basic social equipment, mobility and urban accessibility and social and political engagement, as well as by analyses on the trajectory of Brazilian public housing policies, legislation related to the urban and housing matter, interacting with public housing residents in order to grasp the meaning of the right to the city from within the living space. As of its hypothesis, it was considered that the way in which public housing is produced, destined to the poor population, follows, in its majority, a pattern that does not respect the families cultural diversity; the units typology does not converse with the subjects needs and the territory selected for construction only meets the capital demand, fostering segregated spaces, causing a mismatch with the right to the city. The methodological path is based on bibliographical, qualitative and empirical research, the last one being the heart of the thesis. The field research evinces the perception of the interlocutor from their social space in the issue of living in a public housing and its relationship to the right to the city, with participants being 18 or over, in working age, residents of the "Cidades Tiradentes" and "Grajaú" districts. It is worth highlighting that the field research was carried out through phone interviews given the COVID-19 pandemic, since the research territories, located in the extreme south and east zones of São Paulo, have dealt with the virus in a more severe manner. To sum up, the analyses evince that housing in the "Cidades Tiradentes" and "Grajaú" districts show the need to rethink the present housing production. The current way poorly converses to the right to the city and reflects spatial, social class, social participation and racialethnical segregation. Therefore, in conclusion, it is urgent to review public power strategies in order to reconstruct urban spaces, under democratic and social justice criteria in order to guarantee housing access and the full exercise of the right to the city